Easter basket murder - Meier, Leslie; Hollis, Lee; Ross, Barbara, 1953- (Kensington Books, 2024)
A collection of Easter-themed mysteries set in coastal Maine features sleuths from three best-selling cozy mystery series: Lucy Stone, Hayley Powell and Julia Snowden, who investigate a deadly art theft and a body that mysteriously vanishes after being discovered.